2017
DOI: 10.22159/ajpcr.2017.v10i3.15972
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Adverse Drug Reactions in a Tertiary Care Teaching Hospital: A Cross-Sectional Study

Abstract: Objective: The aim of this study was to carry out adverse drug reactions (ADRs) monitoring in various departments of a tertiary care teaching hospital. Methods:A cross-sectional study was conducted on ADRs reported in the hospital from December 2012 to May 2013 after obtaining Institutional Ethics Committee approval.Results: A total of 40 ADRs were reported, 47.50% were males and 52.50% were females. The female adult population was 45%. The majority of ADRs were due to antimicrobial agents especially beta-lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Its use in the treatment of ulcers, leprosy, jaundice and its hypoglycemic and analgesic effects are well known [17][18][19][20]. Leaves of Abutilon indicum are known to contain naturally occurring components like flavonoids, alkaloids, tannins, triterpenoids and glycosides [21].…”
Section: Introductionmentioning
confidence: 99%
“…Its use in the treatment of ulcers, leprosy, jaundice and its hypoglycemic and analgesic effects are well known [17][18][19][20]. Leaves of Abutilon indicum are known to contain naturally occurring components like flavonoids, alkaloids, tannins, triterpenoids and glycosides [21].…”
Section: Introductionmentioning
confidence: 99%
“…These results do not support previous findings that female gender is a risk factor for the development of adverse drug reactions. 13 The incidence of ADRs was more in general medicine department this can be related to more inflow of patients in that department. This was also observed in study done by Raja and Venkatasubbaiah et al 13,14 In this study, skin and appendages constituted the most common system affected, accounting for (59.2%) of total ADRs reported with the predominant symptom being skin rashes seen in 44 (31.7%) of the patients, urticaria in 10 (7.2%).…”
Section: Discussionmentioning
confidence: 96%
“…13 The incidence of ADRs was more in general medicine department this can be related to more inflow of patients in that department. This was also observed in study done by Raja and Venkatasubbaiah et al 13,14 In this study, skin and appendages constituted the most common system affected, accounting for (59.2%) of total ADRs reported with the predominant symptom being skin rashes seen in 44 (31.7%) of the patients, urticaria in 10 (7.2%). This is in congruence with studies conducted earlier by Kumar et al and Bhabhor et al 2,15 However, Abhishake et al, and Sajin et al, reported different results, documenting gastrointestinal problems to be 39% and 33%, respectively, being most prevalent manifestation among patients with reported ADR.…”
Section: Discussionmentioning
confidence: 96%
“…Today's pharmaceutical industries are looking for new ways to cut cost and shorten time for the development of drugs while simultaneously improving the quality of their products. The high-performance liquid chromatography is a well-established reliable technique used in controlling the quality and consistency of active pharmaceutical ingredients and dosage forms, it is one of the most promising developments in the area of fast chromatographic separations with its unique characteristics of high chromatographic resolution, speed, and sensitivity analysis [1]. In the present work, this technology has been applied to the method development and validation study of mixture of ramipril and felodipine.…”
Section: Introductionmentioning
confidence: 99%